Diaphragm, preparation method thereof and lithium ion battery

By introducing hydrogen-containing polysiloxane compounds and side-alkenyl groups into the lithium-ion battery separator, and using a catalyst to promote the addition reaction, the self-healing ability of the separator is achieved, solving the problem that the existing separator is prone to rupture at high temperatures, and improving the safety of the battery.

CN119725997APending Publication Date: 2025-03-28SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411812699.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The separator of existing lithium-ion batteries is prone to thermal shrinkage and thermal rupture at high temperatures, resulting in safety hazards and cannot be repaired by itself.

Method used

Using a separator consisting of a first coating, a base film layer and a second coating, the first coating contains a hydrogen-containing polysiloxane compound, and the second coating contains a side alkenyl group-containing polysiloxane compound and a catalyst, and the addition reaction is promoted through the laminated structure and the catalyst to achieve self-healing.

Benefits of technology

The heat resistance and self-repair capability of the diaphragm are improved, and the risk of short circuit caused by contact between the positive electrode plate and the negative electrode plate is reduced, thereby improving the safety of lithium-ion batteries at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725997A_ABST
    Figure CN119725997A_ABST
Patent Text Reader

Abstract

The invention provides a diaphragm, a preparation method thereof and a lithium ion battery. The diaphragm comprises a first coating, a base membrane layer and a second coating which are sequentially stacked, wherein the first coating comprises a first polysiloxane compound, and the second coating comprises a second polysiloxane compound and a catalyst; the first polysiloxane compound is selected from a hydrogen-containing polysiloxane compound, the hydrogen-containing polysiloxane compound comprises a silicon-hydrogen bond, and a side chain of the second polysiloxane compound comprises alkenyl of C2-C6. When the diaphragm is heated and broken, the first coating and the second coating on the two sides of the base film layer are in contact at the broken part, so that the hydrogen-containing polysiloxane compound containing a silicon-hydrogen bond in the first coating and the second polysiloxane compound containing an alkenyl group in the side chain in the second coating are subjected to an addition reaction under the catalysis of a catalyst to generate an addition product; the addition product generated in situ can play a role in repairing the diaphragm, so that the self-repairing of the diaphragm is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery manufacturing, and in particular to a diaphragm, a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium-ion batteries usually include an electrode assembly, a container for accommodating the electrode assembly, and an electrolyte. Among them, the electrode assembly includes two electrodes with opposite polarities and a diaphragm for preventing a short circuit between the two electrodes. Existing diaphragms usually use polyolefin organic diaphragms such as polyethylene or polypropylene. However, this type of diaphragm has a low melting point and poor thermal stability. Its melting temperature is between 130 and 150°C, and its membrane breaking temperature is between 200 and 240°C. With the current higher requirements for lithium-ion batteries in terms of high energy density, high current, and fast charging, in this case, a higher temperature will be generated during the battery charging and discharging process, which is likely to cause the diaphragm to gradually shrink and break, thereby causing the positive and negative electrodes to contact and short-circuit, which in turn causes the battery to burn or explode, causing a safety accident.

[0003] In order to solve the above problems of polyolefin organic diaphragms, some researchers have proposed a solution of coating the organic diaphragms with ceramic coatings. However, the current commercial ceramic diaphragms still have the problem of easy shrinkage at high temperatures. When the temperature reaches the rupture temperature, the diaphragm is prone to rupture, causing a short circuit inside the lithium-ion battery, thus posing a safety hazard.

[0004] In summary, researching and developing a diaphragm that is not easy to shrink at high temperatures (≥130°C) and has self-healing function is of great significance for improving the safety of lithium-ion batteries at high temperatures. Summary of the invention

[0005] The main purpose of the present invention is to provide a diaphragm, a preparation method thereof and a lithium-ion battery, so as to solve the problem that commercial ceramic diaphragms in the prior art have poor heat resistance, are prone to thermal shrinkage and thermal rupture, and cannot achieve self-repair after thermal rupture, resulting in poor safety performance of lithium-ion batteries.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a diaphragm on one hand, which includes a first coating layer, a base film layer and a second coating layer stacked in sequence; wherein the first coating layer includes a first polysiloxane compound, and the second coating layer includes a second polysiloxane compound and a catalyst; the first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, the hydrogen-containing polysiloxane compounds include silicon-hydrogen bonds, and the side chains of the second polysiloxane compounds include C2 to C6 alkenyl groups.

[0007] Furthermore, the first polysiloxane compound includes a polysiloxane compound having a structure represented by formula (I) and / or a polysiloxane compound having a structure represented by formula (II);

[0008]

[0009] Wherein, R1 and R2 are each independently selected from a hydrogen atom or a C2-C6 alkenyl group, and at least one of R1 and R2 is a hydrogen atom; n is any integer from 2 to 999, preferably from 2 to 150;

[0010]

[0011] Among them, R3 and R4 are each independently selected from a hydrogen atom, a C1-C5 alkyl group or a C2-C6 alkenyl group; x1 is any integer from 10 to 1000, preferably 10 to 100; y1 is any integer from 0 to 100, preferably 0 to 50.

[0012] Furthermore, the second polysiloxane compound has a structure shown in formula (III):

[0013]

[0014] Among them, R5 and R7 are each independently selected from a hydrogen atom, an alkyl group of C1 to C5 or an alkenyl group of C2 to C6; R6 is selected from an alkenyl group of C2 to C6; x2 is any integer from 10 to 1000, preferably 10 to 100; y2 is any integer from 0 to 100, preferably 0 to 50; y2 is 0, and R5 and R7 are each independently an alkenyl group of C2 to C6.

[0015] Furthermore, the first polysiloxane compound is selected from one or more of the group consisting of SH-900 terminal hydrogen-containing silicone oil, MHX-1107 polymethyl hydrogen siloxane, XJY-701 polymethyl hydrogen siloxane and XJY-702 methyl-terminated methyl hydrogen siloxane.

[0016] Furthermore, the second polysiloxane compound is selected from one or more of the group consisting of bis-VI-100 vinyl-terminated silicone oil, RH-VI321 vinyl silicone oil and SH-401 vinyl silicone oil.

[0017] Furthermore, a first ceramic layer is provided on a surface of the first coating layer away from the base film layer, and a second ceramic layer is provided on a surface of the second coating layer away from the base film layer; preferably, the thickness of the first ceramic layer and the second ceramic layer are each independently 1 to 5 μm; preferably, the materials of the first ceramic layer and the second ceramic layer include ceramic particles.

[0018] Furthermore, the thickness of the base film layer is 5 to 12 μm; preferably, the material of the base film layer is selected from one or more of the group consisting of polyethylene, polypropylene and polytetrafluoroethylene.

[0019] Furthermore, the thickness of the first coating layer is 1 to 3 μm, and / or the thickness of the second coating layer is 1 to 3 μm.

[0020] Further, the catalyst is a platinum catalyst; preferably, the platinum catalyst is selected from one or more of the group consisting of a platinum-ruthenium catalyst, a platinum / alumina catalyst and a platinum / silicon dioxide catalyst.

[0021] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a method for preparing the above-mentioned diaphragm provided by the present application, and the preparation method of the diaphragm includes: step S1, mixing a first polysiloxane compound with a first solvent to obtain a first dispersed adhesive solution; step S2, mixing a second polysiloxane compound, a catalyst and a second solvent to obtain a second dispersed adhesive solution; step S3, coating the first dispersed adhesive solution on one side surface of the base film layer, obtaining a first coating after a first drying, coating the second dispersed adhesive solution on the other side surface of the base film layer, obtaining a second coating after a second drying; or, coating the second dispersed adhesive solution on one side surface of the base film layer, obtaining a second coating after a third drying, coating the first dispersed adhesive solution on the other side surface of the base film layer, obtaining a first coating after a fourth drying; or, coating the first dispersed adhesive solution and the second dispersed adhesive solution on both side surfaces of the base film layer, respectively, obtaining a first coating and a second coating after a fifth drying.

[0022] Further, step S1 includes: mixing a first polysiloxane compound, an inhibitor, a tackifier, a first dispersant and a first solvent to obtain a first dispersed colloid; preferably, the mass concentration of the first polysiloxane compound in the first dispersed colloid is 10 to 50 g / L; preferably, the weight ratio of the first polysiloxane compound, the inhibitor and the tackifier is (98.79 to 99.70):(0.001 to 0.01):(0.3 to 1.2); preferably, the weight ratio of the first polysiloxane compound to the first dispersant is (97 to 99.5):(0.5 to 3).

[0023] Furthermore, the first polysiloxane compound is selected from one or more of the group consisting of SH-900 end-containing hydrogen silicone oil, MHX-1107 polymethyl hydrogen siloxane, XJY-701 polymethyl hydrogen siloxane and XJY-702 methyl-terminated methyl hydrogen siloxane; preferably, the first polysiloxane compound is a combination of XJY-701 polymethyl hydrogen siloxane, SH-900 end-containing hydrogen silicone oil and MHX-1107 polymethyl hydrogen siloxane, and the weight ratio of the three is (25-80):(10-30):(1-5).

[0024] Further, step S2 includes: mixing a second polysiloxane compound, a catalyst, a second dispersant and a second solvent to obtain a second dispersed colloid; preferably, the mass concentration of the second polysiloxane compound in the second dispersed colloid is 10 to 50 g / L; preferably, the weight ratio of the second polysiloxane compound to the catalyst is (99 to 99.99):(0.01 to 1); preferably, the weight ratio of the second polysiloxane compound to the second dispersant is (97 to 99.5):(0.5 to 3).

[0025] Further, the inhibitor is selected from one or more of the group consisting of cyclohexyl-dimethylsiloxane polymer, eicosyl-dimethylsiloxane polymer, and tri-(methylphosphoryl)oxypropylsiloxane.

[0026] Furthermore, the tackifier is selected from polyvinylidene fluoride and / or polyacrylic acid.

[0027] Further, the first dispersant and the second dispersant are each independently selected from one or more of the group consisting of polyethylene glycol, hydroxyethyl methylcellulose, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0028] Furthermore, the first solvent and the second solvent are independently selected from water and / or N-methylpyrrolidone.

[0029] Furthermore, the coating amount of the first dispersed adhesive and the second dispersed adhesive on the surface of the base film layer is independently 3 to 10 g / cm 2 .

[0030] Furthermore, the temperatures of the first drying, the second drying, the third drying, the fourth drying and the fifth drying are each independently selected from 60 to 90° C., and the times are each independently 30 to 180 seconds.

[0031] Furthermore, the preparation method of the diaphragm also includes: step S4, mixing ceramic particles, a third dispersant, a binder and a third solvent to obtain a slurry; step S5, coating the slurry on the surface of the first coating layer away from the base film layer, obtaining a first ceramic layer after a sixth drying, and coating the slurry on the surface of the second coating layer away from the base film layer, obtaining a second ceramic layer after a seventh drying; preferably, the weight ratio of the ceramic particles, the third dispersant, the binder and the third solvent is (5-15): (1.5-5): (1.5-5): (75-92); preferably, the coating amount of the slurry on the surface of the first coating layer and the second coating layer is independently 2-10 g / cm 2 ; Preferably, the D50 of the ceramic particles is 3 to 15 μm.

[0032] Further, the third dispersant is selected from one or more of the group consisting of polyethylene glycol, hydroxyethyl methylcellulose and polyvinyl alcohol; preferably, the binder is selected from polyvinylidene fluoride and / or polyacrylic acid; preferably, the third solvent is water.

[0033] Furthermore, the sixth drying and the seventh drying are performed at temperatures of 60 to 90° C. and for times of 30 to 180 seconds, respectively, independently of each other.

[0034] Another aspect of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the separator is the above-mentioned separator provided in the present application.

[0035] Applying the technical solution of the present invention, the diaphragm provided in the present application includes a first coating layer containing a first polysiloxane compound, a base film layer, and a second coating layer containing a second polysiloxane compound and a catalyst, which are stacked in sequence, wherein the first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, and the hydrogen-containing polysiloxane compound includes a silicon-hydrogen bond, and the side chain of the second polysiloxane compound includes a C2 to C6 alkenyl group. The introduction of the first polysiloxane compound and the second polysiloxane compound can improve the heat resistance of the first coating and the second coating, thereby improving the heat resistance of the diaphragm and inhibiting the thermal shrinkage of the diaphragm due to heat; at the same time, when the temperature rises, the diaphragm is heated and breaks, and the first coating on both sides of the base film layer contacts the second coating at the rupture, and the hydrogen-containing polysiloxane compound containing silicon-hydrogen bonds in the first coating and the second polysiloxane compound containing alkenyl groups in the side chain in the second coating react under the catalysis of the catalyst to generate addition products, and the in-situ generated addition products can play a role in repairing the diaphragm and realize self-repair of the diaphragm, thereby inhibiting the short circuit inside the lithium-ion battery caused by the contact between the positive electrode and the negative electrode, thereby improving the safety of lithium-ion batteries at high temperatures (≥130°C). BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0037] Figure 1 A schematic diagram of a laminated structure of a diaphragm in one embodiment of the present application is shown;

[0038] Figure 2 A schematic diagram of a laminated structure of a diaphragm in another embodiment of the present application is shown;

[0039] Figure 3 A scanning electron microscope image (SEM image) of the cross section of the diaphragm prepared in Example 1 of the present application is shown.

[0040] The above drawings include the following reference numerals:

[0041] 10. First coating layer; 20. Base film layer; 30. Second coating layer; 40. First ceramic layer; 50. Second ceramic layer. DETAILED DESCRIPTION

[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0043] As described in the background technology, existing commercial ceramic diaphragms have poor heat resistance, are prone to thermal shrinkage and thermal rupture, and cannot achieve self-repair after thermal rupture, resulting in poor safety performance of lithium-ion batteries. In order to solve the above technical problems, the present application provides a diaphragm, such as Figure 1 As shown, the diaphragm includes a first coating layer 10, a base film layer 20 and a second coating layer 30 which are stacked in sequence; wherein the first coating layer 10 includes a first polysiloxane compound, and the second coating layer 30 includes a second polysiloxane compound and a catalyst; the first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, the hydrogen-containing polysiloxane compounds include silicon-hydrogen bonds, and the side chains of the second polysiloxane compounds include C2 to C6 alkenyl groups.

[0044] The present application provides a diaphragm, such as Figure 1 As shown, it includes a first coating layer 10 containing a first polysiloxane compound, a base film layer 20 and a second coating layer 30 containing a second polysiloxane compound and a catalyst, which are stacked in sequence, wherein the first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, and the hydrogen-containing polysiloxane compounds include silicon-hydrogen bonds, and the side chains of the second polysiloxane compounds include C2 to C6 alkenyl groups. The introduction of the first polysiloxane compound and the second polysiloxane compound can improve the heat resistance of the first coating 10 and the second coating 30, thereby improving the heat resistance of the diaphragm and inhibiting the thermal shrinkage of the diaphragm due to heat; at the same time, when the temperature rises, the diaphragm is heated and breaks, and at this time, the first coating 10 and the second coating 30 on both sides of the base film layer 20 are in contact at the rupture, and the hydrogen-containing polysiloxane compound containing silicon-hydrogen bonds in the first coating 10 and the second polysiloxane compound containing alkenyl groups in the side chain in the second coating 30 react under the catalysis of the catalyst to generate addition products, and the in-situ generated addition products can play a role in repairing the diaphragm and realize self-repair of the diaphragm, thereby inhibiting the short circuit inside the lithium-ion battery caused by the contact between the positive electrode and the negative electrode, thereby improving the safety of lithium-ion batteries at high temperatures (≥130°C).

[0045] In a preferred embodiment, the first polysiloxane compound includes a polysiloxane compound having a structure represented by formula (I) and / or a polysiloxane compound having a structure represented by formula (II);

[0046] Wherein, R1 and R2 independently include but are not limited to hydrogen atom or C2-C6 alkenyl, and at least one of R1 and R2 is a hydrogen atom; n is any integer from 2 to 999, preferably 2 to 150;

[0047] Wherein, R3 and R4 each independently include but are not limited to a hydrogen atom, a C1-C5 alkyl group or a C2-C6 alkenyl group; x1 is any integer from 10 to 1000, preferably 10 to 100; y1 is any integer from 0 to 100, preferably 0 to 50.

[0048] Compared with other types, introducing a polysiloxane compound having a structure represented by formula (I) and / or formula (II) into the first coating 10 is beneficial to improving the chemical stability of the first coating 10, and is beneficial to improving the heat resistance of the first coating 10, thereby helping to inhibit thermal shrinkage of the diaphragm when heated, and is also beneficial to introducing more silicon-hydrogen bonds into the first coating 10, thereby facilitating their function when the diaphragm is heated and breaks, which is beneficial to improving the reaction efficiency of the addition reaction, and further, is beneficial to improving the self-repair efficiency of the diaphragm, thereby improving the safety of lithium-ion batteries at high temperatures.

[0049] Compared with other ranges, limiting n in formula (I) within the above range is beneficial to improving the chemical stability of the first polysiloxane compound, and is beneficial to improving the structural stability of the addition reaction product generated during the self-repairing process, thereby helping to improve the efficiency of the self-repairing.

[0050] Compared with other ranges, limiting x1 and y1 in formula (II) within the above range is beneficial to improving the chemical stability of the first polysiloxane compound, and is beneficial to improving the structural stability of the addition reaction product generated during the self-repair process. It is also beneficial to introduce more silicon-hydrogen bonds into the first coating 10, so that it can play a role when the diaphragm is heated and ruptured, thereby improving the reaction efficiency of the addition reaction, and then helping to improve the self-repair efficiency of the diaphragm, and improving the safety of lithium-ion batteries at high temperatures.

[0051] In order to further improve the chemical stability and heat resistance of the first coating 10, further introduce more silicon-hydrogen bonds into the first coating 10, so as to facilitate its role in subsequent processes, further improve the reaction efficiency of the addition reaction, and further improve the self-repair efficiency of the diaphragm, preferably, the first polysiloxane compound includes but is not limited to SH-900 terminal hydrogen-containing silicone oil (Shanghai Chu Yijiajia), MHX-1107 polymethyl hydrogen siloxane (Dow Corning), XJY-701 polymethyl hydrogen siloxane (Jiangxi Xinjiayi) and XJY-702 methyl-terminated methyl hydrogen siloxane (Jiangxi Xinjiayi) One or more of the group consisting of.

[0052] In a preferred embodiment, the second polysiloxane compound has a structure shown in formula (III):

[0053] Among them, R5 and R7 each independently include but are not limited to hydrogen atom, C1~C5 alkyl or C2~C6 alkenyl; R6 includes but is not limited to C2~C6 alkenyl; x2 is any integer from 10 to 1000, preferably 10 to 100; y2 is any integer from 0 to 100, preferably 10 to 50; y2 is 0, R5 and R7 each independently are C2~C6 alkenyl.

[0054] Compared with other types, introducing the polysiloxane compound having the structure shown in formula (III) into the second coating 30 is beneficial to improving the chemical stability of the second coating 30, and is beneficial to improving the heat resistance of the second coating 30, thereby helping to inhibit the thermal shrinkage of the diaphragm when heated, and is also beneficial to introducing more olefin groups into the second coating 30, so that it is easier for it to play a role when the diaphragm is heated and breaks, which is beneficial to improving the reaction efficiency of the addition reaction, and then It is beneficial to improve the self-repair efficiency of the diaphragm and improve the safety of lithium-ion batteries at high temperatures.

[0055] Compared with other ranges, limiting x2 and y2 in formula (II) within the above range is beneficial to improving the chemical stability of the second polysiloxane compound, and is beneficial to improving the structural stability of the addition reaction product generated during the self-healing process. It is also beneficial to introduce more olefin groups into the second coating 30, so that it can play a role when the diaphragm is heated and ruptured, thereby helping to improve the reaction efficiency of the addition reaction, and then helping to improve the self-healing efficiency of the diaphragm and improve the safety of lithium-ion batteries at high temperatures.

[0056] In order to further improve the chemical stability and heat resistance of the second coating 30, more olefin groups are further introduced into the second coating 30, so as to facilitate its role in subsequent processes, further improve the reaction efficiency of the addition reaction, and further improve the self-repair efficiency of the diaphragm. Preferably, the second polysiloxane compound includes but is not limited to one or more of the group consisting of double VI-100 terminal vinyl silicone oil (Hongyuan New Materials), RH-VI321 vinyl silicone oil (Zhejiang Runhe) and SH-401 vinyl silicone oil (Shanghai Chuyijiajia).

[0057] In a preferred embodiment, Figure 2 As shown, a first ceramic layer 40 is disposed on the surface of the first coating layer 10 away from the base film layer 20, and a second ceramic layer 50 is disposed on the surface of the second coating layer 30 away from the base film layer 20. The provision of the first ceramic layer 40 and the second ceramic layer 50 is conducive to improving the heat resistance of the diaphragm, and is conducive to improving the mechanical strength of the diaphragm, thereby helping to improve the safety of lithium-ion batteries at high temperatures.

[0058] In order to further improve the heat resistance and mechanical strength of the separator, and thus further improve the safety of lithium-ion batteries at high temperatures, preferably, the thickness of the first ceramic layer 40 and the second ceramic layer 50 are independently 1 to 5 μm.

[0059] In order to further improve the heat resistance and mechanical strength of the diaphragm, in a preferred embodiment, the materials of the first ceramic layer 40 and the second ceramic layer 50 include ceramic particles, a third dispersant and a binder. Preferably, the weight ratio of the ceramic particles, the third dispersant and the binder is (5-15):(1.5-5):(1.5-5).

[0060] In a preferred embodiment, the ceramic particles are alumina ceramic particles and / or boehmite ceramic particles commonly used in the art, wherein the content of alumina is ≥ 99.5wt% based on the weight percentage of the alumina ceramic particles; and the content of monohydrated aluminum oxide is ≥ 99.5wt% based on the weight percentage of the boehmite ceramic particles. The use of the above-mentioned types of ceramic particles is conducive to further improving the heat resistance and mechanical strength of the diaphragm.

[0061] In a preferred embodiment, the thickness of the base film layer 20 is 5 to 12 μm. The thickness of the base film layer 20 includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the mechanical strength of the diaphragm, and is beneficial to preventing the diaphragm from rupturing or being pierced by the electrode material during use, and is also beneficial to improving the transmission efficiency of lithium ions, thereby improving the charging and discharging efficiency and electrochemical performance of the lithium ion battery.

[0062] In order to further improve the mechanical strength of the diaphragm and further improve the transmission efficiency of lithium ions, thereby further improving the charge and discharge efficiency and electrochemical performance of lithium-ion batteries, preferably, the material of the base film layer 20 includes but is not limited to one or more of the group consisting of polyethylene, polypropylene and polytetrafluoroethylene.

[0063] In a preferred embodiment, the thickness of the first coating 10 is 1 to 3 μm. The thickness of the first coating 10 includes but is not limited to the above range. Limiting it within the above range is conducive to improving the heat resistance of the first coating 10, thereby improving the heat resistance of the diaphragm, and inhibiting the thermal shrinkage of the diaphragm when heated. It is also conducive to introducing a more suitable amount of the first polysiloxane compound, thereby facilitating the reaction efficiency of the addition reaction, and improving the self-repairing efficiency of the diaphragm, and further facilitating the use safety of the lithium-ion battery at high temperatures.

[0064] In order to improve the heat resistance of the second coating 30, improve the heat resistance of the diaphragm, and introduce a more suitable amount of the second polysiloxane compound, thereby further improving the reaction efficiency of the addition reaction, further improving the self-repair efficiency of the diaphragm, and further improving the safety of lithium-ion batteries at high temperatures, in a preferred embodiment, the thickness of the second coating 30 is 1 to 3 μm.

[0065] In a preferred embodiment, the catalyst is a platinum catalyst. Compared with other types, the platinum catalyst is conducive to improving the reaction efficiency of the addition reaction between the hydrogen-containing polysiloxane compound in the first coating 10 and the second polysiloxane compound in the second coating 30, thereby helping to improve the self-repairing efficiency of the diaphragm, and further helping to improve the safety of lithium-ion batteries at high temperatures.

[0066] In order to further improve the reaction efficiency of the addition reaction occurring when the first coating 10 and the second coating 30 come into contact when the diaphragm is broken, thereby further improving the self-repair efficiency of the diaphragm, and further improving the safety of lithium-ion batteries at high temperatures, preferably, the platinum catalyst includes but is not limited to one or more of the group consisting of platinum ruthenium (Pt / Ru) catalysts, platinum / alumina catalysts (Pt / Al2O3) and platinum / silicon dioxide catalysts (Pt / SiO2).

[0067] The second aspect of the present application also provides a method for preparing the above-mentioned diaphragm provided by the present application, and the preparation method of the diaphragm includes: step S1, mixing a first polysiloxane compound with a first solvent to obtain a first dispersed adhesive solution; step S2, mixing a second polysiloxane compound, a catalyst and a second solvent to obtain a second dispersed adhesive solution; step S3, coating the first dispersed adhesive solution on one side surface of the base film layer 20, obtaining a first coating 10 after a first drying, coating the second dispersed adhesive solution on the other side surface of the base film layer 20, obtaining a second coating 30 after a second drying; or, coating the second dispersed adhesive solution on one side surface of the base film layer 20, obtaining a second coating 30 after a third drying, coating the first dispersed adhesive solution on the other side surface of the base film layer 20, obtaining a first coating 10 after a fourth drying; or, coating the first dispersed adhesive solution and the second dispersed adhesive solution on both side surfaces of the base film layer 20 respectively, obtaining a first coating 10 and a second coating 30 after a fifth drying.

[0068] Step S1 and step S2 in the present application can obtain a first dispersed adhesive solution containing a first polysiloxane compound and a second dispersed adhesive solution containing a second polysiloxane compound, which are convenient for coating them on both sides of the base film layer 20 in step S3 to obtain a first coating layer 10 and a second coating layer 30. The first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, and the hydrogen-containing polysiloxane compound includes a silicon-hydrogen bond, and the side chain of the second polysiloxane compound includes a C2-C6 alkenyl group. Introducing the first polysiloxane compound and the second polysiloxane compound into the first coating 10 and the second coating 30 can improve the heat resistance of the first coating 10 and the second coating 30, thereby improving the heat resistance of the diaphragm and inhibiting the thermal shrinkage of the diaphragm due to heat; at the same time, when the temperature continues to rise and the diaphragm is broken by heat, the first coating 10 and the second coating 30 coated on both sides of the base film layer 20 can contact at the rupture, so that the hydrogen-containing polysiloxane compound containing silicon-hydrogen bonds in the first coating 10 and the second polysiloxane compound containing alkenyl groups in the side chain in the second coating 30 react under the catalysis of the catalyst to generate addition products, and the in-situ generated addition products can play a role in repairing the diaphragm and realize self-repair of the diaphragm, thereby inhibiting the short circuit inside the lithium-ion battery caused by the contact between the positive electrode and the negative electrode, thereby improving the safety of lithium-ion batteries at high temperatures (≥130°C).

[0069] Compared with other coating methods, the above coating method can obtain a first coating 10 and a second coating 30 with uniform thickness, which can be in uniform contact when the diaphragm is broken, thereby improving the reaction efficiency of the addition reaction and further improving the self-repair efficiency of the diaphragm.

[0070] In a preferred embodiment, step S1 includes: mixing a first polysiloxane compound, an inhibitor, a tackifier, a first dispersant and a first solvent to obtain a first dispersed colloid. Introducing an inhibitor when preparing the first dispersed colloid is beneficial to inhibiting a violent reaction when the first coating 10 contacts the second coating 30 when the diaphragm breaks, thereby facilitating the inhibition of local overheating and incomplete reaction caused by local violent reactions; the introduction of a tackifier is beneficial to improving the processability of the first dispersed colloid, facilitating subsequent coating thereof on the surface of the base film layer 20 to obtain the first coating 10; the introduction of a first dispersant is beneficial to improving the dispersibility of each component in the first dispersed colloid, thereby facilitating the dispersibility of each component in the first coating 10, facilitating its function when the diaphragm breaks.

[0071] In order to further inhibit the violent reaction caused by the contact between the first coating 10 and the second coating 30 when the diaphragm ruptures, thereby further inhibiting the occurrence of local overheating and incomplete reaction caused by local violent reaction, preferably, the inhibitor includes but is not limited to one or more of the group consisting of cyclohexyl-dimethylsiloxane polymer, eicosyl-dimethylsiloxane polymer, and tri-(methylphosphoryl)oxypropylsiloxane.

[0072] In order to further improve the processability of the first dispersed adhesive and to facilitate coating it on the surface of the base film layer 20 to obtain the first coating 10, preferably, the tackifier includes but is not limited to polyvinylidene fluoride and / or polyacrylic acid.

[0073] In a preferred embodiment, the mass concentration of the first polysiloxane compound in the first dispersed colloid is 10 to 50 g / L. The mass concentration of the first polysiloxane compound in the first dispersed colloid includes but is not limited to the above range, and limiting it within the above range is conducive to introducing a more suitable amount of the first polysiloxane compound into the first dispersed colloid, and is conducive to improving the dispersion uniformity of each component in the first dispersed colloid, thereby facilitating the first coating 10 to play its role when the membrane is broken, and is conducive to improving the reaction efficiency of the addition reaction, and further conducive to improving the self-repair efficiency of the membrane.

[0074] In a preferred embodiment, the weight ratio of the first polysiloxane compound, the inhibitor and the tackifier is (98.79-99.70): (0.001-0.01): (0.3-1.2); the weight ratio of the first polysiloxane compound to the first dispersant is (97-99.5): (0.5-3). The weight ratio of each component in the first dispersed colloid includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the utilization rate of each component, introducing a more suitable amount of the first polysiloxane compound into the first dispersed colloid, improving the chemical stability of the first coating 10, and improving the dispersion uniformity of each component in the first dispersed colloid, so as to facilitate the first coating 10 to play its role when the membrane breaks, and to improve the reaction efficiency of the addition reaction, and then to improve the self-repair efficiency of the membrane.

[0075] In order to further improve the chemical stability and heat resistance of the first coating 10, further introduce more silicon-hydrogen bonds into the first coating 10, so as to facilitate its role in subsequent processes, further improve the reaction efficiency of the addition reaction, and further improve the self-repair efficiency of the diaphragm, in a preferred embodiment, the first polysiloxane compound includes but is not limited to SH-900 terminal hydrogen-containing silicone oil (Shanghai Chu Yijiajia), MHX-1107 polymethyl hydrogen siloxane (Dow Corning), XJY-701 polymethyl hydrogen siloxane (Jiangxi Xinjiayi) and XJY-702 methyl-terminated methyl hydrogen siloxane (Jiangxi Xinjiayi) One or more of the group consisting of.

[0076] In order to further introduce a more suitable amount of hydrogen-containing polysiloxane compounds and further introduce more silicon-hydrogen bonds so that they can play a role when the diaphragm ruptures, and at the same time to further improve the chemical stability of the first coating 10, preferably, the first polysiloxane compound is a combination of XJY-701 polymethyl hydrogen siloxane (Jiangxi Xinjiayi), SH-900 end-hydrogenated silicone oil (Shanghai Chuyijiajia) and MHX-1107 polymethyl hydrogen siloxane (Dow Corning), and the weight ratio of the three is (25~80):(10~30):(1~5).

[0077] In a preferred embodiment, step S2 includes: mixing a second polysiloxane compound, a catalyst, a second dispersant and a second solvent to obtain a second dispersed colloid. Introducing the second dispersant when preparing the second dispersed colloid is beneficial to improving the dispersibility of each component in the second dispersed colloid, thereby improving the dispersibility of each component in the second coating 30, so that it is convenient for it to play a role when the membrane breaks.

[0078] In order to further improve the dispersion uniformity of each component in the first dispersed colloid and the second dispersed colloid, to facilitate obtaining the first coating 10 and the second coating 30 and to make them play a role when the membrane ruptures, preferably, the first dispersant and the second dispersant each independently include but are not limited to sodium carboxymethyl cellulose and / or acrylic dispersants, more preferably, the acrylic dispersant includes but is not limited to one or more of the group consisting of polyethylene glycol, hydroxyethyl methyl cellulose, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0079] In a preferred embodiment, the mass concentration of the second polysiloxane compound in the second dispersed colloid is 10 to 50 g / L. The mass concentration of the second polysiloxane compound in the second dispersed colloid includes but is not limited to the above range, and limiting it within the above range is conducive to introducing a more suitable amount of the second polysiloxane compound into the second dispersed colloid, thereby facilitating the reaction efficiency of the addition reaction, and further facilitating the self-repair efficiency of the diaphragm.

[0080] In a preferred embodiment, the weight ratio of the second polysiloxane compound to the catalyst is (99-99.99):(0.01-1). The weight ratio of the second polysiloxane compound to the catalyst includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the catalytic efficiency of the catalyst for the addition reaction, and is beneficial to improving the reaction efficiency of the addition reaction, thereby helping to improve the self-repair efficiency of the diaphragm.

[0081] In order to improve the dispersion uniformity of each component in the second dispersed colloid solution, thereby further improving the reaction efficiency of the addition reaction, in a preferred embodiment, the weight ratio of the second polysiloxane compound to the second dispersant is (97-99.5):(0.5-3).

[0082] In order to improve the dispersibility of each component in the first dispersed colloid and the second dispersed colloid, and to facilitate coating them on the surface of the base film layer 20 to obtain the first coating 10 and the second coating 30, preferably, the first solvent and the second solvent independently include but are not limited to water and / or N-methylpyrrolidone (NMP).

[0083] In order to further improve the heat resistance of the first coating 10 and the second coating 30, thereby further improving the heat resistance of the coating, further inhibiting the thermal shrinkage of the diaphragm when heated, and further introducing a more suitable amount of the first polysiloxane compound and the second polysiloxane compound, thereby further improving the reaction efficiency of the addition reaction and further improving the self-repairing efficiency of the diaphragm, preferably, the coating amount of the first dispersed adhesive and the second dispersed adhesive on the surface of the base film layer 20 is independently 3 to 10 g / cm 2 .

[0084] In order to improve the solvent removal rate in the first coating 10 and the second coating 30, in a preferred embodiment, the temperatures of the first drying, the second drying, the third drying, the fourth drying and the fifth drying are independently including but not limited to 60-90°C, and the time is independently 30-180s.

[0085] In a preferred embodiment, the preparation method of the diaphragm also includes: step S4, mixing ceramic particles, a third dispersant, a binder and a third solvent to obtain a slurry; step S5, coating the slurry on the side surface of the first coating 10 away from the base film layer 20, and obtaining the first ceramic layer 40 after the sixth drying, and coating the slurry on the side surface of the second coating 30 away from the base film layer 20, and obtaining the second ceramic layer 50 after the seventh drying.

[0086] Step S4 can obtain a slurry containing ceramic particles, which is convenient for coating the slurry on the surface of the first coating layer 10 away from the base film layer 20 and the surface of the second coating layer 30 away from the base film layer 20 in step S5, respectively, to obtain the first ceramic layer 40 and the second ceramic layer 50. The introduction of the third dispersant when preparing the slurry is conducive to improving the dispersibility of each component in the slurry; the introduction of the binder is conducive to fixing the ceramic particles, improving the bonding effect between the ceramic particles, and obtaining a stable first ceramic layer 40 and the second ceramic layer 50, thereby improving the heat resistance and mechanical strength of the first ceramic layer 40 and the second ceramic layer 50, and then improving the heat resistance and mechanical strength of the diaphragm, and improving the safety of lithium-ion batteries at high temperatures.

[0087] In a preferred embodiment, the weight ratio of the ceramic particles, the third dispersant, the binder and the third solvent is (5-15): (1.5-5): (1.5-5): (75-92). The weight ratio of the ceramic particles, the third dispersant, the binder and the third solvent includes but is not limited to the above range. Limiting it to the above range is beneficial to improving the utilization rate of each component, improving the bonding effect between ceramic particles, and obtaining a uniformly dispersed slurry, thereby facilitating obtaining a stable first ceramic layer 40 and a second ceramic layer 50.

[0088] In a preferred embodiment, the coating amount of the slurry on the surface of the first coating 10 and the second coating 30 is independently 2 to 10 g / cm 2 The coating amount of the slurry on the surface of the first coating layer 10 and the second coating layer 30 includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the compactness of the first ceramic layer 40 and the second ceramic layer 50, and at the same time is beneficial to improving the heat resistance and mechanical strength of the first ceramic layer 40 and the second ceramic layer 50, thereby improving the heat resistance and mechanical strength of the diaphragm.

[0089] In order to further improve the compactness of the first ceramic layer 40 and the second ceramic layer 50, further improve the heat resistance and mechanical strength of the first ceramic layer 40 and the second ceramic layer 50, thereby further improving the heat resistance and mechanical strength of the diaphragm, preferably, the D50 of the ceramic particles is 3 to 15 μm.

[0090] In order to further improve the dispersion uniformity of each component in the slurry, thereby facilitating the coating of the slurry, preferably, the third dispersant includes but is not limited to one or more of the group consisting of polyethylene glycol, hydroxyethyl methyl cellulose and polyvinyl alcohol.

[0091] In order to further fix the ceramic particles and obtain a more stable first ceramic layer 40 and second ceramic layer 50, preferably, the binder includes but is not limited to polyvinylidene fluoride and / or polyacrylic acid.

[0092] In order to further improve the dispersion uniformity of each component in the slurry, preferably, the third solvent is water.

[0093] In a preferred embodiment, the temperature of the sixth drying and the seventh drying are independently 60 to 90° C., and the time is independently 30 to 180 seconds. The temperature and time of the sixth drying and the seventh drying include but are not limited to the above ranges, and limiting them to the above ranges is conducive to improving the solvent removal rate in the first ceramic layer 40 and the second ceramic layer 50.

[0094] The third aspect of the present application also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the separator is the above-mentioned separator provided in the present application.

[0095] The above-mentioned diaphragm provided in the present application has good heat resistance and self-repairing function. On the one hand, it can inhibit the thermal shrinkage of the diaphragm due to heat. On the other hand, when the temperature continues to rise, the diaphragm is heated and breaks, the first coating 10 and the second coating 30 on both sides of the base film layer 20 in the diaphragm can contact at the rupture point, and the hydrogen-containing polysiloxane compound containing silicon-hydrogen bonds in the first coating 10 and the second polysiloxane compound containing alkenyl groups in the side chain in the second coating 30 react under the catalysis of the catalyst to generate an addition product. The in-situ generated addition product can play a role in repairing the diaphragm, thereby realizing the self-repair of the diaphragm and inhibiting the short circuit inside the lithium-ion battery caused by the contact between the positive electrode and the negative electrode. The above-mentioned diaphragm is used in lithium-ion batteries to improve the safety of lithium-ion batteries at high temperatures (≥130°C).

[0096] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0097] Example 1

[0098] A method for preparing a diaphragm comprises the following steps:

[0099] (1) placing a first polysiloxane compound, an inhibitor cyclohexyl-dimethylsiloxane polymer (weight average molecular weight of 3000), a tackifier polyvinylidene fluoride (weight average molecular weight of 8000) and a dispersant polyacrylic acid (weight average molecular weight of 1000) in a weight ratio of 99.5:0.01:0.49:0.5 and 500 mL of water in a blender, stirring at 25° C. and 500 rpm for 12 h to obtain a first dispersed rubber solution; wherein, The mass concentration of the first polysiloxane compound in the first dispersed colloid is 30 g / L, and the composition of the first polysiloxane compound is XJY-701 polymethyl hydrogen siloxane (Jiangxi Xinjiayi, hydrogen content is 1.6wt%), SH-900 terminal hydrogenated silicone oil (Shanghai Chuyijia, hydrogen content is 0.1wt%) and MHX-1107 polymethyl hydrogen siloxane (Dow Corning, hydrogen content is 1.8wt%), and the weight ratio of the three is 68:25:5;

[0100] (2) placing SH-401 vinyl silicone oil (Shanghai Chuyijia, linear type, vinyl content of 8 wt%), Pt / Al2O3 catalyst (Pt loading of 0.5 wt%) and dispersant polyacrylic acid (weight average molecular weight of 1000) in a weight ratio of 98.5:0.5:1.0 and 500 mL of water in a blender, stirring at 25° C. and 500 rpm for 8 h to obtain a second dispersed colloid; wherein the mass concentration of the second polysiloxane compound in the second dispersed colloid is 25 g / L;

[0101] (3) The first dispersed adhesive prepared in step (1) is coated on one side of the 9 μm thick polyethylene-based film layer at a coating amount of 3 g / cm 2 , dried at 85° C. for 2 min to obtain a first coating 10 with a thickness of 1 μm;

[0102] (4) The second dispersed rubber solution prepared in step (2) was coated on the other side of the 9 μm thick polyethylene-based film layer at a coating amount of 3 g / cm 2 , dried at 85°C for 2 min to obtain a second coating 30 with a thickness of 1 μm;

[0103] (5) Ceramic particles (boehmite ceramic particles, Anhui Yishitong Materials, BG-613, D50 is 3.5 μm) with a weight ratio of 5:1.5:1.5, dispersant polyacrylic acid (weight average molecular weight is 1000) and binder polyvinylidene fluoride (weight average molecular weight is 8000) are placed in a blender with 500 mL of water, and stirred at 25 ° C and 1000 rpm for 8 h to obtain a slurry;

[0104] (6) The slurry prepared in step (5) is applied to the surface of the first coating layer 10 away from the polyethylene-based film layer, and the coating amount is 4 g / cm 2 , dried at 85° C. for 3 min to obtain a first ceramic layer 40 with a thickness of 1.5 μm;

[0105] (7) The slurry prepared in step (5) is applied to the surface of the second coating layer 30 away from the polyethylene-based film layer, and the coating amount is 4 g / cm 2 , and dried at 85° C. for 3 min to obtain a second ceramic layer 50 with a thickness of 1.5 μm, thereby obtaining a diaphragm.

[0106] like Figure 2 As shown, the laminated structure of the diaphragm prepared in Example 1 can be expressed as: first ceramic layer 40 / first coating layer 10 / base film layer 20 / second coating layer 30 / second ceramic layer 50.

[0107] The scanning electron microscope image of the cross section of the diaphragm prepared in Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that the boundary between the base film layer 20 and the first coating layer 10 and the second coating layer 30 is not obvious, and they are all organic matter, but the boundary between the base film layer 20 and the first ceramic layer 40 and the second ceramic layer 50 is obvious.

[0108] Example 2

[0109] The difference from Example 1 is that step (5), step (6) and step (7) are omitted, that is, the prepared diaphragm does not contain the first ceramic layer 40 and the second ceramic layer 50, and the remaining steps are the same as Example 1.

[0110] Example 3

[0111] The difference from Example 1 is that in step (1), the mass concentration of the first polysiloxane compound in the first dispersed adhesive solution is 10 g / L, and the remaining steps are the same as Example 1.

[0112] Example 4

[0113] The difference from Example 1 is that in step (1), the mass concentration of the first polysiloxane compound in the first dispersed adhesive solution is 50 g / L, and the remaining steps are the same as Example 1.

[0114] Example 5

[0115] The difference from Example 1 is that in step (1), the mass concentration of the first polysiloxane compound in the first dispersed adhesive solution is 6 g / L, and the remaining steps are the same as Example 1.

[0116] Example 6

[0117] The difference from Example 1 is that in step (2), the mass concentration of the second polysiloxane compound in the second dispersed colloid is 10 g / L, and the remaining steps are the same as Example 1.

[0118] Example 7

[0119] The difference from Example 1 is that in step (2), the mass concentration of the second polysiloxane compound in the second dispersed colloid is 50 g / L, and the remaining steps are the same as Example 1.

[0120] Example 8

[0121] The difference from Example 1 is that in step (2), the mass concentration of the second polysiloxane compound in the second dispersed colloid is 8 g / L, and the remaining steps are the same as Example 1.

[0122] Example 9

[0123] The difference from Example 1 is that in step (1), an equal amount of SH-900 end-hydrogenated silicone oil is used to replace the combination of XJY-701 polymethyl hydrogen siloxane, SH-900 end-hydrogenated silicone oil and MHX-1107 polymethyl hydrogen siloxane, that is, the first polysiloxane compound is only SH-900 end-hydrogenated silicone oil, and the remaining steps are the same as in Example 1.

[0124] Example 10

[0125] The difference from Example 1 is that in step (2), the weight ratio of the second polysiloxane compound to the Pt / Al2O3 catalyst is 99:1, and the remaining steps are the same as Example 1.

[0126] Embodiment 11

[0127] The difference from Example 1 is that in step (2), the weight ratio of the second polysiloxane compound to the Pt / Al2O3 catalyst is 99.99:0.01, and the remaining steps are the same as Example 1.

[0128] Example 12

[0129] The difference from Example 1 is that in step (2), the weight ratio of the second polysiloxane compound to the Pt / Al2O3 catalyst is 98.5:1.5, and the remaining steps are the same as Example 1.

[0130] Comparative Example 1

[0131] A commercial ceramic diaphragm is a double-sided ceramic diaphragm with a laminated structure of: ceramic material layer / polyethylene-based film layer / ceramic material layer, wherein the thickness of the ceramic material layer is 1.5 μm, and the thickness of the polyethylene-based film layer is 9 μm.

[0132] Comparative Example 2

[0133] The difference from Example 1 is that in step (1), an equal amount of double VI-100 vinyl-terminated silicone oil (Hongyuan New Materials, vinyl content of 1.0 wt%) is used as the first polysiloxane compound, and the remaining steps are the same as Example 1.

[0134] Comparative Example 3

[0135] The difference from Example 1 is that an equal amount of dimethyl silicone oil (Anbi Ya, SF350 with a weight average molecular weight of 10000) was used as the second polysiloxane compound, and the remaining steps were the same as those in Example 1.

[0136] Comparative Example 4

[0137] The difference from Example 1 is that no Pt / Al2O3 catalyst is added in step (2), and the remaining steps are the same as Example 1.

[0138] Comparative Example 5

[0139] The difference from Example 1 is that the first dispersed adhesive is coated on both sides of the polyethylene-based film layer 20 , and the remaining steps are the same as those of Example 1.

[0140] The performance test of the diaphragms prepared in all the examples and comparative examples of the present application was carried out, and the test method was as follows:

[0141] The initial air permeability of the diaphragm was tested according to the air permeability test method in GB / T 36363-2018; a diaphragm with a length of 300 mm was taken and subjected to a tensile test using a thermomechanical analyzer (TMA) at a test temperature range of 50 to 300°C, and the deformation temperature curve of the diaphragm was recorded. The temperature corresponding to the instantaneous increase in the slope of the deformation temperature curve was the rupture temperature of the diaphragm; after the diaphragm was left for a period of time to self-repair, the air permeability of the self-repaired diaphragm was tested according to the air permeability test method in GB / T 36363-2018. If the air permeability after self-repair is close to the initial air permeability and the self-repair time is short, it means that the diaphragm has good self-repair performance.

[0142] The test results are shown in Table 1.

[0143] Table 1

[0144]

[0145]

[0146] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0147] By comparing Example 1 and Comparative Examples 1 to 5, it can be seen that the first polysiloxane compound and the second polysiloxane compound of the above-mentioned type of the present application are introduced into the diaphragm. When the diaphragm is heated and ruptured, the first coating 10 on both sides of the base film layer 20 contacts the second coating 30 at the rupture, and the hydrogen-containing polysiloxane compound containing silicon-hydrogen bonds in the first coating 10 and the second polysiloxane compound containing alkenyl groups in the side chain in the second coating 30 undergo addition reaction under the catalysis of the catalyst to generate addition products. The in-situ generated addition products can play a role in repairing the diaphragm, thereby realizing self-repair of the diaphragm.

[0148] By comparing Examples 1 and 2, it can be seen that the provision of the first ceramic layer 40 and the second ceramic layer 50 is beneficial to improving the heat resistance of the diaphragm, improving the mechanical strength of the diaphragm, and inhibiting the flow of the first coating 10 and the second coating 30 after heating, thereby helping to improve the reaction efficiency of the addition reaction, and further helping to improve the self-repair efficiency of the diaphragm.

[0149] By comparing Examples 1, 3 to 5, it can be seen that, compared with other ranges, limiting the mass concentration of the first polysiloxane compound in the first dispersed colloid within the above range is beneficial to introducing a more suitable amount of the first polysiloxane compound into the first dispersed colloid, which is beneficial to improving the dispersion uniformity of the components in the first dispersed colloid, thereby facilitating the first coating 10 to play its role when the diaphragm ruptures, and is beneficial to improving the reaction efficiency of the addition reaction, thereby helping to improve the self-repair efficiency of the diaphragm.

[0150] By comparing Examples 1, 6 to 8, it can be seen that, compared with other ranges, limiting the mass concentration of the second polysiloxane compound in the second dispersed colloid solution to the above range is beneficial to introducing a more suitable amount of the second polysiloxane compound into the second dispersed colloid solution, thereby helping to improve the reaction efficiency of the addition reaction, and further helping to improve the self-repair efficiency of the diaphragm.

[0151] By comparing Examples 1 and 9, it can be seen that, compared with other types, limiting the first polysiloxane compound to a combination of XJY-701 polymethyl hydrogen siloxane (Jiangxi Xinjiayi), SH-900 end-hydrogenated silicone oil (Shanghai Chuyijiajia) and MHX-1107 polymethyl hydrogen siloxane (Dow Corning) is beneficial to introducing a more suitable amount of hydrogen-containing polysiloxane compounds into the first coating 10, thereby introducing more silicon-hydrogen bonds, which can play a role when the diaphragm is broken, thereby helping to improve the self-repair efficiency of the diaphragm.

[0152] By comparing Examples 1 and 10 to 12, it can be seen that, compared with other ranges, limiting the weight ratio of the second polysiloxane compound to the catalyst within the above-mentioned range of the present application is beneficial to improving the catalytic efficiency of the catalyst for the addition reaction, which is beneficial to improving the reaction efficiency of the addition reaction, thereby helping to improve the self-repair efficiency of the diaphragm.

[0153] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A diaphragm, characterized in that: The diaphragm comprises a first coating layer (10), a base film layer (20) and a second coating layer (30) which are stacked in sequence; wherein the first coating layer (10) comprises a first polysiloxane compound, and the second coating layer (30) comprises a second polysiloxane compound and a catalyst; the first polysiloxane compound is selected from hydrogen-containing polysiloxane compounds, the hydrogen-containing polysiloxane compound comprises a silicon-hydrogen bond, and the side chain of the second polysiloxane compound comprises a C2 to C6 alkenyl group.

2. The diaphragm according to claim 1, characterized in that The first polysiloxane compound includes a polysiloxane compound having a structure represented by formula (I) and / or a polysiloxane compound having a structure represented by formula (II); Wherein, R1 and R2 are each independently selected from a hydrogen atom or a C2-C6 alkenyl group, and at least one of R1 and R2 is a hydrogen atom; n is any integer from 2 to 999, preferably from 2 to 150; Among them, R3 and R4 are each independently selected from a hydrogen atom, a C1-C5 alkyl group or a C2-C6 alkenyl group; x1 is any integer from 10 to 1000, preferably 10 to 100; y1 is any integer from 0 to 100, preferably 0 to 50.

3. The diaphragm according to claim 1 or 2, characterized in that: The second polysiloxane compound has a structure shown in formula (III): Wherein, R5 and R7 are each independently selected from a hydrogen atom, a C1-C5 alkyl group or a C2-C6 alkenyl group; R6 is selected from a C2-C6 alkenyl group; x2 is any integer from 10 to 1000, preferably 10 to 100; y2 is any integer from 0 to 100, preferably 0 to 50; y2 is 0, and R5 and R7 are each independently a C2-C6 alkenyl group; Preferably, the first polysiloxane compound is one or more selected from the group consisting of SH-900 terminal hydrogen-containing silicone oil, MHX-1107 polymethyl hydrogen siloxane, XJY-701 polymethyl hydrogen siloxane and XJY-702 methyl-terminated methyl hydrogen siloxane; Preferably, the second polysiloxane compound is one or more selected from the group consisting of bis-VI-100 vinyl-terminated silicone oil, RH-VI321 vinyl silicone oil and SH-401 vinyl silicone oil.

4. The diaphragm according to any one of claims 1 to 3, characterized in that A first ceramic layer (40) is provided on a surface of the first coating layer (10) that is away from the base film layer (20), and a second ceramic layer (50) is provided on a surface of the second coating layer (30) that is away from the base film layer (20); Preferably, the thickness of the first ceramic layer (40) and the second ceramic layer (50) are independently 1 to 5 μm; Preferably, the materials of the first ceramic layer (40) and the second ceramic layer (50) include ceramic particles.

5. The diaphragm according to claim 1, characterized in that The thickness of the base film layer (20) is 5 to 12 μm; and / or the thickness of the first coating layer (10) is 1 to 3 μm; and / or the thickness of the second coating layer (30) is 1 to 3 μm; Preferably, the material of the base film layer (20) is selected from one or more of the group consisting of polyethylene, polypropylene and polytetrafluoroethylene; Preferably, the catalyst is a platinum catalyst; preferably, the platinum catalyst is one or more selected from the group consisting of a platinum-ruthenium catalyst, a platinum / alumina catalyst and a platinum / silicon dioxide catalyst.

6. A method for preparing a diaphragm according to any one of claims 1 to 5, characterized in that: The preparation method of the diaphragm comprises: Step S1, mixing a first polysiloxane compound with a first solvent to obtain a first dispersed adhesive solution; Step S2, mixing a second polysiloxane compound, a catalyst and a second solvent to obtain a second dispersed rubber solution; Step S3, coating the first dispersed adhesive on one side of the base film layer (20), and obtaining a first coating layer (10) after a first drying, and coating the second dispersed adhesive on the other side of the base film layer (20), and obtaining a second coating layer (30) after a second drying; or, The second dispersed adhesive liquid is coated on one side of the base film layer (20), and after a third drying, a second coating layer (30) is obtained; the first dispersed adhesive liquid is coated on the other side of the base film layer (20), and after a fourth drying, a first coating layer (10) is obtained; or, The first dispersed adhesive liquid and the second dispersed adhesive liquid are respectively coated on both side surfaces of the base film layer (20), and after a fifth drying, a first coating layer (10) and a second coating layer (30) are obtained.

7. The method for preparing a diaphragm according to claim 6, characterized in that: The step S1 comprises: mixing the first polysiloxane compound, an inhibitor, a tackifier, a first dispersant and the first solvent to obtain the first dispersed adhesive solution; Preferably, the mass concentration of the first polysiloxane compound in the first dispersed colloid is 10-50 g / L; preferably, the weight ratio of the first polysiloxane compound, the inhibitor and the tackifier is (98.79-99.70):(0.001-0.01):(0.3-1.2); preferably, the weight ratio of the first polysiloxane compound to the first dispersant is (97-99.5):(0.5-3); Preferably, the first polysiloxane compound is one or more selected from the group consisting of SH-900 hydrogen-terminated silicone oil, MHX-1107 polymethyl hydrogen siloxane, XJY-701 polymethyl hydrogen siloxane and XJY-702 methyl-terminated methyl hydrogen siloxane; preferably, the first polysiloxane compound is a combination of XJY-701 polymethyl hydrogen siloxane, SH-900 hydrogen-terminated silicone oil and MHX-1107 polymethyl hydrogen siloxane, and the weight ratio of the three is (25-80):(10-30):(1-5); Preferably, the step S2 comprises: mixing the second polysiloxane compound, the catalyst, the second dispersant and the second solvent to obtain the second dispersed rubber solution; More preferably, the mass concentration of the second polysiloxane compound in the second dispersed colloid is 10-50 g / L; preferably, the weight ratio of the second polysiloxane compound to the catalyst is (99-99.99):(0.01-1); preferably, the weight ratio of the second polysiloxane compound to the second dispersant is (97-99.5):(0.5-3); Preferably, the inhibitor is selected from one or more of the group consisting of cyclohexyl-dimethylsiloxane polymer, eicosyl-dimethylsiloxane polymer, and tri-(methylphosphoryl)oxypropylsiloxane; Preferably, the tackifier is selected from polyvinylidene fluoride and / or polyacrylic acid; More preferably, the first dispersant and the second dispersant are each independently selected from one or more of the group consisting of polyethylene glycol, polyacrylic acid, hydroxyethyl methyl cellulose, polyvinyl alcohol and sodium carboxymethyl cellulose; Preferably, the first solvent and the second solvent are independently selected from water and / or N-methylpyrrolidone.

8. The method for preparing a diaphragm according to claim 6, characterized in that: The coating amounts of the first dispersed adhesive solution and the second dispersed adhesive solution on the surface of the base film layer (20) are independently 3 to 10 g / cm 2 ; Preferably, the temperatures of the first drying, the second drying, the third drying, the fourth drying and the fifth drying are each independently selected from 60 to 90° C., and the times are each independently 30 to 180 seconds.

9. The method for preparing a diaphragm according to any one of claims 6 to 8, characterized in that: The method for preparing the diaphragm further comprises: Step S4, mixing the ceramic particles, the third dispersant, the binder and the third solvent to obtain a slurry; Step S5, coating the slurry on the surface of the first coating layer (10) away from the base film layer (20), and obtaining a first ceramic layer (40) after a sixth drying, and coating the slurry on the surface of the second coating layer (30) away from the base film layer (20), and obtaining a second ceramic layer (50) after a seventh drying; Preferably, the weight ratio of the ceramic particles, the third dispersant, the binder and the third solvent is (5-15):(1.5-5):(1.5-5):(75-92); Preferably, the coating amount of the slurry on the surface of the first coating (10) and the second coating (30) is independently 2 to 10 g / cm 2 ; Preferably, the sixth drying and the seventh drying are each independently performed at a temperature of 60 to 90° C. and each independently performed for 30 to 180 seconds; Preferably, the D50 of the ceramic particles is 3 to 15 μm; Preferably, the third dispersant is selected from one or more of the group consisting of polyethylene glycol, hydroxyethyl methylcellulose and polyvinyl alcohol; Preferably, the binder is selected from polyvinylidene fluoride and / or polyacrylic acid; Preferably, the third solvent is water.

10. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The separator is the separator according to any one of claims 1 to 5.